Legal philosophy and the challenges of biosciences / edited by Jerzy Stelmach, Marta Soniewicka, Wojciech Załuski. - Stelmach, Jerzy; Soniewicka, Marta; Załuski, Wojciech (Studies in the philosophy of law, 2010)
The present book is the fourth volume of the series Studies in the Philosophy of Law which has appeared since 2001. The previous two volumes had a monographic character, the last one being devoted to the topic of the economic analysis of law and published in English. The present volume also has a monographic character and concerns various issues of bioethics, law and philosophy.